2019
DOI: 10.3892/ol.2019.11075
|View full text |Cite
|
Sign up to set email alerts
|

BATF acts as an oncogene in non‑small cell lung cancer

Abstract: One of the main causes of cancer incidence and mortality worldwide is lung cancer. This study focused on the function of basic leucine zipper ATF-like transcription factor (BATF) in non-small cell lung cancer (NSCLC). Using NSCLC patient data from The Cancer Genome Atlas, the present study demonstrated that BATF expression in NSCLC tissues was significantly higher compared with that in adjacent non-tumor tissues (P=6.56x10-6). Lentivirus-mediated short hairpin RNA (shRNA) was used to knock down BATF expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 30 publications
3
25
0
Order By: Relevance
“…Further, as NFkB is suggested to drive TAMs towards a more anti-inflammatory environment, it is plausible that this subpopulation plays a role in the observed peripheral cells' evolution towards an anti-inflammatory environment. Furthermore the enrichment of other transcription factors from the same cluster (BATF, PLXNC1, MTF1) as NFkB have been shown to upregulate in other cancers [72][73][74] suggesting NFkB to exert and a pro-tumor effect.…”
Section: Discussionmentioning
confidence: 99%
“…Further, as NFkB is suggested to drive TAMs towards a more anti-inflammatory environment, it is plausible that this subpopulation plays a role in the observed peripheral cells' evolution towards an anti-inflammatory environment. Furthermore the enrichment of other transcription factors from the same cluster (BATF, PLXNC1, MTF1) as NFkB have been shown to upregulate in other cancers [72][73][74] suggesting NFkB to exert and a pro-tumor effect.…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies suggest that BATF may influence the development of different types of cancer, including non-small cell lung cancer (NSCLC), lymphoma, and multiple myeloma (36,37). Such as, BATF might active NSCLC cell proliferation and apoptosis in BATF-silenced A549 cells (38). In addition, BATF is a gene that inhibits T cell function, inhibitory receptors can cause T cell exhaustion by upregulating BATF (39).…”
Section: Discussionmentioning
confidence: 99%
“…The BATF gene acts a pivotal part in the development of different types of cancer, including colon cancer, lymphoma, and multiple myeloma [ 41 43 ]. In addition, Feng et al found that BATF acted as an oncogene in non-small-cell lung cancer [ 44 ]. In this study, the joint survival analyses revealed that the BATF gene was closely related with poor prognosis in patients with ccRCC ( Figure 9(e) ).…”
Section: Discussionmentioning
confidence: 99%